Unbury carol ebook A novel. - Malerman, Josh (2018)
The New York Times bestselling author of Bird Box returns with a supernatural thriller  of love, redemption, and murder. NAMED ONE OF THE BEST BOOKS OF THE YEAR BY NEWSWEEK “This one haunts you for reasons you can’t quite put your finger on. . . . [Josh Malerman] defies categories and comparisons with other writers.” — Kirkus Reviews Carol Evers is a woman with a dark secret. She has died many times . . . but her many deaths are not final: They are comas, a waking slumber indistinguishable from death, each lasting days. Only two people know of Carol’s eerie condition. One is her husband, Dwight, who married Carol for her fortune, and—when she lapses into another coma—plots to seize it by proclaiming her dead and quickly burying her . . . alive. The other is her lost love, the infamous outlaw James Moxie. When word of Carol’s dreadful fate reaches him, Moxie rides the Trail again to save his beloved from an early, unnatural grave. And all the while, awake and aware, Carol fights to free herself from the crippling darkness that binds her—summoning her own fierce will to survive. As the players in this drama of life and death fight to decide her fate, Carol must in the end battle to save herself. The haunting story of a woman literally bringing herself back from the dead, Unbury Carol is a twisted take on the Sleeping Beauty fairy tale that will stay with you long after you’ve turned the final page. Praise for Unbury Carol “Fantastically clever. A breakneck ride to save a life already lost, proving sometimes death is only the beginning.” —J. D. Barker, internationally bestselling author of  The Fourth Monkey “Breathtaking and menacing . . . an intricately plotted, lyrical page-turner about love, betrayal, revenge, and the primal fear of being buried alive.” — Booklist (starred review) “Unbury Carol is a Poe story set in the weird West we all carry inside us, and it not only hits the ground running, it digs into that ground, too. About six wonderful feet.” —Stephen Graham Jones, author of Mongrels “Bleakly lyrical à la Cormac McCarthy and Flannery O’Connor.” — Library Journal (starred review) “With vivid prose and characters that leap off the page, guns a-blazing, Unbury Carol creates its own lingering legend, dragging you along like an obstinate horse toward a righteous storm of an ending.” —Delilah S. Dawson, New York Times bestselling author of Star Wars: Phasma